Recent Advances in Supercritical CO2 Extraction of Pigments, Lipids and Bioactive Compounds from Microalgae - Soultana Tzima; Ioulia Georgiopoulou; Vasiliki Louli; Kostis Magoulas (Molecules, 2023)
Supercritical CO2 extraction is a green method that combines economic and environmental benefits. Microalgae, on the other hand, is a biomass in abundance, capable of providing a vast variety of valuable compounds, finding applications in the food industry, cosmetics, pharmaceuticals and biofuels. An extensive study on the existing literature concerning supercritical fluid extraction (SFE) of microalgae has been carried out focusing on carotenoids, chlorophylls, lipids and fatty acids recovery, as well as the bioactivity of the extracts. Moreover, kinetic models used to describe SFE process and experimental design are included. Finally, biomass pretreatment processes applied prior to SFE are mentioned, and other extraction methods used as benchmarks are also presented.